2020
DOI: 10.1016/j.redox.2019.101395
|View full text |Cite
|
Sign up to set email alerts
|

Ketone bodies, stress response, and redox homeostasis

Abstract: The ketone body β-hydroxybutyrate is no longer viewed simply as a metabolic intermediate, as it regulates a broad range of physiological processes at cellular and systemic levels. Particularly, β-hydroxybutyrate functions as a stress response molecule and orchestrates an antioxidant defense program to maintain redox homeostasis in response to environmental and metabolic challenges, such as ischemia. This property of β-hydroxybutyrate might be key for the beneficial effect of calorie restriction on stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 29 publications
1
65
0
2
Order By: Relevance
“…Ketone bodies may regulate ROS balance through direct and indirect pathways. This is supported by in vitro studies, showing that ketone bodies may function as direct antioxidants, suppressing mitochondrial ROS production and promoting transcriptional activity of the antioxidant defence [ 76 ]. Haces et al [ 77 ] demonstrated that both the L- and D-isoform of BHB and acetoacetate possess direct scavenging effects on ROS (BHB effects were specific to hydroxyl radicals).…”
Section: The Effect Of Ketone Bodies On Brain Metabolismmentioning
confidence: 94%
See 1 more Smart Citation
“…Ketone bodies may regulate ROS balance through direct and indirect pathways. This is supported by in vitro studies, showing that ketone bodies may function as direct antioxidants, suppressing mitochondrial ROS production and promoting transcriptional activity of the antioxidant defence [ 76 ]. Haces et al [ 77 ] demonstrated that both the L- and D-isoform of BHB and acetoacetate possess direct scavenging effects on ROS (BHB effects were specific to hydroxyl radicals).…”
Section: The Effect Of Ketone Bodies On Brain Metabolismmentioning
confidence: 94%
“…Another in vitro study in neocortical neurons and isolated mitochondria, showed that a combination of BHB and acetoacetate reduced ROS production stimulated by calcium induced glutamate excitotoxicity, and that this effect was due to enhanced NADH oxidation and thus, an increased NAD+/NADH ratio [ 78 ]. Both the increased NAD+/NADH ratio and the BHB itself may stimulate the antioxidant defence system through activation of different transcription factors [ 76 , 79 ].…”
Section: The Effect Of Ketone Bodies On Brain Metabolismmentioning
confidence: 99%
“… 55 - 57 It has been widely speculated that some of the benefits associated with caloric restriction are attributed to endogenous production of ketone bodies. 58 - 61 While more data are needed to clarify this relationship, metabolism of R -βHB has been shown to reduce OS 59 and susceptibility to developing several chronic diseases.…”
Section: R -βHb As a Signaling Metabolitementioning
confidence: 99%
“… 51 The oxidation of R -βHB changes cellular ratios of NAD + /NADH which favors redox changes and results in the activation of signaling proteins such as NAD dependent deacetylases (SIRT1, SIRT3) that are known to increase the activity of antioxidants such as heme oxygenase 1, superoxide dismutases, and catalases through the activation of forkhead box O1 and 3 (FOXO1 & FOXO3). 59 It has also been speculated that the mitochondrial consumption of R -βHB activates nuclear factor-erythroid 2-related factor-2 (NRF2) which serves as an additional mechanism for the up-regulation of endogenous antioxidants. 59 Collectively, the potential for R -βHB to act as a direct and indirect antioxidant provides evidence that some of the metabolic benefits with caloric restriction may be attributed directly to R -βHB itself.…”
Section: R -βHb As a Signaling Metabolitementioning
confidence: 99%
See 1 more Smart Citation